Legal Protection for Students as Whistleblowers of Corruption Cases in Universities - Prakasa, Satria Unggul Wicaksana; Rais Alhakim, Eky Karimatur (Universitas Muhammadiyah Yogyakarta, 2024)
A whistleblower is necessary for corruption cases in universities. by emphasizing previous research that discusses related, legal protection for reporters to eradicate corruption about academic freedom. Then, the weak coordination of law enforcement corruption. And the pattern of corruption in universities shows that corruption can concern all professions, including academics. This study aims to make a real contribution to the efforts of ethics enforcement and anti-corruption in the university environment. Increasing legal protection for students as reporters is expected to create a more supportive and safe environment for those who want to disclose corruption. So, the researchers used socio-legal methods in this study. This study highlights the relationship between law and society to create a more complex answer to the problem raised. The results of this research contain conclusions about the difficulty of the active role of students and what legal protection efforts are obtained in combating corruption in universities. This study offers something : (1) barriers and legal protection efforts to students as whistleblowers in eradicating university corruption; (2) on how to handle corruption cases in universities, especially students as reporters. This study concluded that the government and university leaders must be able to provide legal certainty by protecting students as reporters, and those who reveal corruption need to be strengthened to avoid retaliation or intimidation so that students are safer reporting allegations of corruption without fear of facing repression or other reprisals.